“Optimización del sistema de rutas para la recolección de residuos sólidos urbanos en el cantón San Lorenzo, provincia de Esmeraldas” - Alvarez Ortiz, Andrea Elizabeth (2021)
In the solid waste collection system in the San Lorenzo canton there is evidence of a deficiency in the management of the waste generated in the studied area. The present investigation was carried out in order to propose the optimization of routes for the collection of solid waste in the San Lorenzo canton. In the first stage, a diagnosis of the current situation of urban solid waste generated in the study area was carried out, for which an interview was carried out with two public officials of the municipal GAD of the San Lorenzo canton. In addition, through direct observation of the vehicles that carry out the collection, it was possible to know the route they make. Regarding the characterization phase, the delivery of colored covers was made for the respective classification of the waste. This research determined through sampling the feasibility of implementing a proposal based on route optimization for MSW collection. It was possible to know through the data obtained, the analysis of variance and the Tukey test were applied with a 95% confidence interval, it was identified that statistically there is significant variability in terms of the production of organic waste with a representative weight of 62.59% In the same way, it was obtained that ordinary waste represents 24.52% and plastic waste represents 12.89%, obtaining an average daily production of 0.60 kg / person / day. For the modeling of the route with the adequate and efficient conditions of the solid waste collection routes, the redesign of the collection routes was used and through the ArcGIS 10.5 software. The results will help to improve the service, being a viable solution that reflects positive results for the current and future generation of the canton, and it is important that the municipal GAD take into consideration the implementation of public policies aimed at improving the quality of the solid waste collection service. Keywords: Optimization, routes, per-capita production, waste, collection, solid waste management